Inoculation With Desulfovibrio sp. Does Not Enhance Chalk Formation in the Pacific Oyster - Banker, Roxanne M. W.; Coil, David (Frontiers in Marine Science, 2020)
Some oyster species precipitate a soft, friable form of calcite that is occluded within their shells, often referred to as chalk or chalky deposits. Because of the unusual microstructure of this shell feature, it has been proposed that chalk is the result of microbial involvement in the calcification process. Specifically, chalk has been hypothesized to be induced or influenced by microbial sulfate-reduction, and therefore chalk formation may not be under direct control of the oysters themselves. Specimens of the Pacific oyster, Magallana gigas, well known for chalk deposition within shells, were grown in Bodega Harbor, Bodega Bay, California and exposed monthly to treatments that altered the abundance of sulfate-reducing bacteria within oysters. The four treatment conditions evaluated included a control group (not exposed to any reagents), as well as oysters exposed to ciprofloxacin (a broad spectrum antibiotic), sodium molybdate (a compound known to inhibit bacterial sulfate reduction), and an inoculum of a sulfate-reducing bacterium isolated for this study. At the end of a 7 month growing period, specimens were culled and shells from treatment groups were assessed for chalk content by measuring bulk shell density and percentage of chalk in a cross sectional area. While analyses show that treatment conditions were successful with respect to altering abundances of sulfate-reducing bacteria in oysters, increasing SRB populations did not correlate to enhanced chalk expression in oyster shells. Therefore, chalk formation in oysters is not induced by the activity of sulfate-reducing bacteria within the oyster. Interestingly, control oysters produced more chalk than the other treatment groups, according to both bulk shell density and percent chalk measured in cross section. Given that control oysters represent the wild type for chalk expression in shells, it is inferred that the decreased formation of chalk in the other groups was due to a perturbation of the microbiome in the oyster calcifying fluid. However, the methods used here only quantify the presence of sulfate-reducing bacteria in oysters, and therefore, additional work is necessary to evaluate the role of the microbiome in oyster calcification.